Method of iterative single-channel blind separation for qpsk signals - Semenov, V.Yu. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2018)
A method for single-channel blind separation of two QPSK (quadrature phase shift keying) signals is proposed. The method is based on the iterative maximization of a posteriori probability for mixture's components. The relations for a posteriori probabilities are derived and on its basis the iterative algorithm for the estimation of mixture's components is developed. The algorithm for the estimation of channel parameters (amplitudes, phases, time delays) is also developed. The effectiveness of method is demonstrated for various noise levels and time diversities between channels. The proposed parameters’ estimation procedure provides significant reduction of bit error rate (BER) over the case of unknown parameters.